Factors Associated with the Giving of Basic Inactivated Poliovirus Vaccine (IPV) Immunisation - Zulianti, Resillia; Novitry, Fera; Oktavia, Lina (Lentera Perawat, 2024)
Inactivated Poliovirus Vaccine (IPV) immunisation is given starting from 2-3 months of age with three consecutive doses with an interval of 6-8 weeks. IPV immunisation is one of the key steps in polio control efforts. However, there are still challenges in achieving optimal immunisation coverage in some areas. The aim was to determine the factors associated with the provision of IPV basic immunisation. This type of research uses descriptive analytics with a Cross Sectional approach where data on both variables are collected at the same time or at one time. Sampling using simple random sampling using the formula as many as 164 samples. The instruments used in the study were questionnaires and KMS Statistical tests used were chi-square. Results: The results of this study report that there is a significant relationship between knowledge (p value 0.000), work (p value 0.000), posyandu cadres (p value 0.000), posyandu officers (p value 0.000), and family support (p value 0.000) with the provision of IPV Basic Immunisation in the Working Area of Puskesmas Pulau Panggung. There is an influence of knowledge, occupation, posyandu cadres, posyandu officers, and family support on the provision of IPV basic immunisation. This study suggests that health workers should be more active in providing information to local mothers by providing information through counselling and putting up posters, banners and distributing leaflets about the importance of IPV to children or by providing information from house to house.